The parental irresponsibility and social consequences - Llanos Chávez, Graciela Esther (2008)
Father, mother and child form a triad of biopsychosocial development in constant motion, having the State as the guaranteeing entity of social coexistence, acting this through different institutions when the parents don't fulfill their children's needs, becoming in parental irresponsibility with unpredictable consequences in the kids' life, which can be seen in many studies carried out in 2005.